Rhole of RhoA-GTPases activator, GEF-H1, in thyroid cancer - Peros, I. G. (2020)
GEF-H1 is a Rho-GTPases activator whose overexpression has been shown to be associated with tumor development. However, its role in thyroid cancer (TC) progression has not yet been stud- ied. TC has been dramatically rising worldwide in recent decades and represents the most prevalent endocrine malignancy. For this reason, we have begun analyzing GEF-H1 expression in human thyroid biopsies. We observed higher cytoplasmic protein concen- tration when comparing by immunohistochemistry tumor tissue (TT) with non-malignant tissue (NMT) (n=52; p=0.0003). Similar results were obtained by Western blot in thyroid biopsies and cancer cell lines. Furthermore, clinical-histopathological data showed signifi- cant GEF-H1 overexpression in TT than NMT (p=7E-07), which cor- relates with a less patient survival (p=0.0088). mRNA data analysis from biopsies (Human Protein Atlas and Oncomine platforms) also showed a significant GEF-H1 overexpression in TT compared with NMT. Analyzing Gene Expression Omnibus microarray data with R language, we observed that GEF-H1 is between 2-17% of the most expressed genes in different TC histotypes. We also determined that GEF-H1 expression is significantly higher in papillary and anaplas- tic carcinomas than NMT (p<0.05) and its expression increased in papillary carcinomas with lymph node invasion and/or metastasis (p<0.001). Moreover, we looked for those genes whose mRNA ex- pression correlates with GEF-H1 and we evaluated their function through gene ontology analysis (DAVID and STRING platforms) and their participation in signaling pathways (KEGG and Reactome). Genes associated with migration, mechanical signaling, cytoskele- ton remodeling and focal adhesions positive correlated with GEF-H1 expression in TC (p<0.001). The results suggest that GEF-H1 might be a potential tumor biomarker and/or therapeutic target in TC, since it would be involved in the pro-tumorigenic signaling by coordinating changes in cell morphology, proliferation, migration and invasion.